Oxalate (dys)Metabolism - Baltazar, Pedro (2023)
Funding Information: The authors would like to thank the Associação Portuguesa de Urologia, for funding the project “Precision Urology: Metabolic Phenotype of Patients with Metabolic Syndrome Traits and Recurrent Nephrolithiasis—Metabolomics and Recurrence Assessment”. iNOVA4Health research program (UIDP/04462/2020) is also acknowledged to support Judit Morello. Publisher Copyright: © 2023 by the authors.